1993
DOI: 10.1159/000119006
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological, Neuroendocrine and Cellular Immune Reactions under Psychological Stress

Abstract: Emotional stress is often followed by increased susceptibility to infections. Natural killer (NK) cells play a major role in the immediate immune response controlling this susceptibility. In this study on 45 first-time parachutists, it is demonstrated that highly controlled psychological stress increased psychophysiological variables, enhanced the secretion of sympathetic-adrenal hormones and also led to a significant increase of NK cells and their cytotoxic activity followed by a decrease below starting value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 7 publications
(7 reference statements)
1
22
0
Order By: Relevance
“…Compared with eumenorrheic women, women with FHA display mild indexes of "psychological stress" in the form of dysfunctional attitudes, difficulty coping with daily hassles, higher dependence on interpersonal relationships, and a higher incidence of past psychiatric disorders (4, 17). However, neuroendocrine abnormalities associated with FHA also indicate metabolic stress (21), and these patients exhibit a high incidence of subclinical eating abnormalities (19,33,37). Similarly, reproductive dysfunction occurring in anorexia nervosa was considered to be primarily the result of severe nutritional stress; yet the propensity to exercise intensively adds to the metabolic imbalance, and food restriction itself has a behavioral, seemingly volitional component that reflects altered cognitions that predispose to psychosocial stress.…”
mentioning
confidence: 99%
“…Compared with eumenorrheic women, women with FHA display mild indexes of "psychological stress" in the form of dysfunctional attitudes, difficulty coping with daily hassles, higher dependence on interpersonal relationships, and a higher incidence of past psychiatric disorders (4, 17). However, neuroendocrine abnormalities associated with FHA also indicate metabolic stress (21), and these patients exhibit a high incidence of subclinical eating abnormalities (19,33,37). Similarly, reproductive dysfunction occurring in anorexia nervosa was considered to be primarily the result of severe nutritional stress; yet the propensity to exercise intensively adds to the metabolic imbalance, and food restriction itself has a behavioral, seemingly volitional component that reflects altered cognitions that predispose to psychosocial stress.…”
mentioning
confidence: 99%
“…Parachute jumping is a well-characterized stress model to study emotional and physical stress in humans (10,11). In the present study, we used this model to determine whether stress in humans affects plasma NGF levels and NGFreceptor (NGF-r) distribution in peripheral blood cells.…”
mentioning
confidence: 99%
“…Involvement of catecholamines in response to psycho logical stress has been demonstrated during tandem jumps in parachutists, with a common significant in crease both in epinephrine and in NE [24], More recently other investigators have reported significant increases in NE during both physical and mental stress [25], In con trast, in our experiment the emotional arousal induced a significant increase in epinephrine plasma levels only, without a significant response in NE, in agreement with other studies utilizing attention and memory stressful challenges [26], Also during public speaking a more signif icant increase in epinephrine than in NE has been demon strated with a dissociation between the secretion of epi nephrine by the adrenal medulla and the secretion of NE by the sympathetic nerve endings [27], GH seems to be particularly sensitive to mood changes and showed a significant response during the violent movie: similar effects of psychological stress on GH plas ma levels have been observed also in many other stressful conditions [14, 21.28],…”
Section: Discussionmentioning
confidence: 99%